Comparison of clinical and radiological outcomes in intertrochanteric fractures treated with InterTAN nail against conventional cephalomedullary nails: a systematic review - Akshay Date; Mrinalini Panthula; Anita Bolina (Future Science OA, 2021)
Intertrochanteric fractures, accountable for 50% of hip fractures, can be fixed with cephalomedullary devices such as Proximal Femoral Nail Antirotation (PFNA™), Gamma3 nailing system and TRIGEN™ InterTAN™ nail (IT). IT uniquely uses two cephalocervical screws that allow for linear compression and provide additional resistance to femoral head rotation. A literature review assessing clinical outcomes of these devices was conducted, with 14 studies enrolling 3104 patients meeting the inclusion criteria. PFNA and Gamma3 had better intraoperative outcomes compared with IT; however, IT had superior implant-related outcomes of cut-out and screw migration. No difference was found between IT and PFNA or Gamma3 in Harris Hip Scores, time to union, malunion and nonunion. Further long-term studies are needed to evaluate clinical outcomes and cost–effectiveness of cephalomedullary devices.